18F-FDG-PET/CT-based treatment planning for definitive (chemo)radiotherapy in patients with head and neck squamous cell carcinoma improves regional control and survival. (January 2020) - van den Bosch, Sven; Doornaert, Patricia A.H.; Dijkema, Tim; Zwijnenburg, Ellen M.; Verhoef, Lia C.G.; Hoeben, Bianca A.W.; Kasperts, Nicolien; Smid, Ernst J.; Terhaard, Chris H.J.; Kaanders, Johannes H.A.M.
Highlights: FDG-PET/CT-based nodal target volume definition improves regional control and survival. No isolated recurrences in the electively treated neck occurred with FDG-PET/CT-based nodal target volume definition. FDG-PET/CT-based nodal target volume definition causes target volume transformation. FDG-PET/CT can guide gradient dose prescription with de-escalation of the elective dose. Abstract: Background and purpose: Multimodality imaging including 18 F-FDG-PET has improved the detection threshold of nodal metastases in head and neck squamous cell carcinoma (HNSCC). The aim of this retrospective analysis is to investigate the impact of FDG-PET/CT-based nodal target volume definition (FDG-PET/CT-based NTV) on radiotherapy outcomes, compared to conventional CT-based nodal target volume definition (CT-based NTV). Materials and methods: Six-hundred-thirty-three patients treated for HNSCC with definitive (chemo)radiotherapy using IMRT/VMAT techniques between 2008 and 2017 were analyzed. FDG-PET/CT-based NTV was performed in 46% of the patients. The median follow-up was 31 months. Diagnostic imaging depicting the regional recurrence was co-registered with the initial CT-scan to reconstruct the exact site of the recurrence. Multivariate Cox regression analysis was performed to identify variables associated with radiotherapy outcome. Results: FDG-PET/CT-based NTV improved control of disease in the CTVelective-nodal (HR: 0.33, p = 0.026), overall regional control (HR: 0.62, p = 0.027) and overall survival (HR: 0.71, p = 0.033) compared to CT-based NTV. The risk for recurrence in the CTVelective-nodal was increased in case of synchronous local recurrence of the primary tumor (HR: 12.4, p < 0.001). Conclusion: FDG-PET/CT-based NTV significantly improved control of disease in the CTVelective-nodal, overall regional control and overall survival compared to CT-based NTV. A significant proportion of CTVelective-nodal recurrences are potentially new nodal manifestations from a synchronous local recurrent primary tumor. These results support the concept of target volume transformation and give an indication of the potential of FDG-PET to guide gradual radiotherapy dose de-escalation in elective neck treatment in HNSCC.